Early-Age Tensile Basic Creep Behavioral Characteristics of High-Strength Concrete Containing Admixtures. (8th May 2019) - Ni, Tongyuan; Yang, Yang; Gu, Chunping; Liu, Jintao; Chen, Jin; Lou, Xiaotian
Abstract : Tensile creep is an important parameter to evaluate cracking probability of high-strength concrete (HSC) structure, and the mineral admixtures have great effect on it. In this paper, the early-age tensile basic creep behaviors of HSC containing fly ash (FA) and blast furnace slag (BS) were investigated by experiments, and the influences of loading age and stress level (stress-strength ratio of initial loading) were evaluated. The results showed that FA promoted the early-age tensile basic creep while BS inhibited the early-age tensile creep. Moreover, the influence of loading age on early-age tensile basic creep of HSC was more significant, and the affected ages' duration was longer than that of plain concrete. The early-age tensile basic creep of HSC containing admixtures also showed linear creep characteristic after a certain age as HSC without admixtures, and the linear characteristic was more obvious at a later loading age. The tensile basic creep velocity of HSC containing FA was the highest, while HSC containing BS exhibited the lowest velocity. The influence of admixtures on velocities of tensile basic creep was gradually attenuated with the age growth in holding period.